Does commuting mode choice impact health?. (3rd November 2020) - Jacob, Nikita; Munford, Luke; Rice, Nigel; Roberts, Jennifer
Abstract: Governments around the world are encouraging people to switch away from sedentary modes of travel towards more active modes, including walking and cycling. The aim of these schemes is to improve population health and to reduce emissions. There is considerable evidence on the latter, but relatively little on the former. This paper investigates the impact of mode choice on physical and mental health. Using data from the UK Household Longitudinal Study, we exploit changes in mode of commute to identify health outcome responses. Individuals who change modes are matched with those whose mode remains constant. Overall we find that mode switches affect both physical and mental health. When switching from car to active travel we see an increase in physical health for women and in mental health for both genders. In contrast, both men and women who switch from active travel to car are shown to experience a significant reduction in their physical health and health satisfaction, and a decline in their mental health when they change from active to public transport.